Structural Evaluation and Optimization of a Peanut Shelling Machine Frame Using Finite Element Analysis - M. Ibnu Hakim; Anrinal Anrinal; Asmara Yanto (Jurnal Teknik Mesin, 2025)
This study investigates the structural integrity of a peanut shelling machine frame with a capacity of 60 kg/hour using Finite Element Analysis (FEA) in SolidWorks. Two configurations of ASTM A36 angle steel profiles—40×40×3 mm and 20×20×3 mm—were evaluated with a frame geometry of 906×600×900 mm. Operational loads were applied to three critical zones with aggregate weights of 82.6 kg, 5.3 kg, and 13.1 kg, respectively. The structural response was assessed through von Mises stress distribution, nodal displacement, and safety factor analysis. Results indicate that the 40×40×3 mm frame exhibits a maximum stress of 37.114 MPa, displacement of 0.2431 mm, and a safety factor of 6.7, while the 20×20×3 mm frame shows a maximum stress of 73.978 MPa, displacement of 0.4521 mm, and a safety factor of 3.4. Both designs satisfy structural safety requirements, maintaining stresses below the material yield strength of 250 MPa and safety factors above the minimum threshold of 2.0. Stress concentrations were predominantly observed at frame corners. While the smaller profile reduces material usage by 50%, it also decreases stiffness by 86%. The findings demonstrate that the 20×20×3 mm configuration is a cost-effective alternative for static loading conditions, whereas the 40×40×3 mm frame provides higher rigidity suitable for potential dynamic load scenarios.